NASKAH DOKUMEN/SURAT RAJA KESULTANAN KALIMANTAN BARAT: KAJIAN STRUKTUR, PALEOGRAFI, DAN KEBAHASAAN (Royal Letter/Document of West Kalimantan Sultanate: Structure, Paleography, and Language) - Muhammad Jaruki (Kandai, 2017)
Issues disclosed in the research are  the structure,  the form and style, and language aspect used in Royal Letter/Document of Pontianak Sultan, West Kalimantan Sultanate. The aim of the research is to discribe and explain structure, the style of writing of Jawi script, and the language used in the script or letter of “Sultan Pontianak, Sultan Syarif Hamid Bin Sultan Syarif U'sman Alqodri to the Government of the Netherlands”. Using content analysis method to describe the structure, style, and language contained in those scripts, and diplomatic method for manuscript editing, the edited text  produced is in accordance with the original. The analysis result shows that the script of "Letter of Agreement of the Dutch government with Pontianak Sultan, Sultan Syarif Hamid bin Sultan Syarif U'sman Alqodri" is classified as official letter which has the structure of (1) letter head, (2) opening words, (3) the contents of the letter, and (4) the date of the letter. Other parts or structure of the letter not included in the script are: mailing address, number of letters, attachments, subject, mailing address, signature, the name of the sender, and stamp. This letter is written mostly in Arabic typed riqa, taqwi, and muluqah. The language used in the script is Arabic and Dutch. The sentences structure of the manuscript however, does not comply with the language rules.